1998
DOI: 10.1037/0021-843x.107.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid mental disorders: Implications for treatment and sample selection.

Abstract: Disorders from the Diagnostic and Statistical Manual of Mental Disorders (3rd ed., rev.; American Psychiatric Association, 1987) were assessed in a birth cohort of 961 young adults. Comorbid cases exceeded single-disordered cases in chronic history of mental illness, use of treatments, physical health problems, functional interference in daily life, and impaired adaptation across domains such as work, education, health, and social-support networks. Single-disorder cases were also more impaired than nondisorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 222 publications
(141 citation statements)
references
References 38 publications
3
137
0
1
Order By: Relevance
“…This overlap is observed at the level of mood, symptoms, and disorder for many of the most common psychiatric disorders among youth, including anxiety, conduct/oppositional defiant, and attention deficit/hyperactivity (ADHD) (Costello et al 2003;Lewinsohn et al 1993;Newman et al 1998; see Hankin and Abela 2005;Rudolph et al 2006, for reviews). For example, a meta analysis (Angold et al 1999) of depression comorbidity with these other symptoms and disorders among community samples revealed that depression was associated with anxiety (median odds ratio=8.2), conduct/oppositional problems (median odds ratio=6.6), and ADHD (median odds ratio=5.5).…”
Section: Introductionmentioning
confidence: 99%
“…This overlap is observed at the level of mood, symptoms, and disorder for many of the most common psychiatric disorders among youth, including anxiety, conduct/oppositional defiant, and attention deficit/hyperactivity (ADHD) (Costello et al 2003;Lewinsohn et al 1993;Newman et al 1998; see Hankin and Abela 2005;Rudolph et al 2006, for reviews). For example, a meta analysis (Angold et al 1999) of depression comorbidity with these other symptoms and disorders among community samples revealed that depression was associated with anxiety (median odds ratio=8.2), conduct/oppositional problems (median odds ratio=6.6), and ADHD (median odds ratio=5.5).…”
Section: Introductionmentioning
confidence: 99%
“…The real importance of epidemiology lies in its ability to yield an unbiased understanding of associations between variables, which is especially important for describing and explaining developmental continuity and change across the life course (Costello & Angold, 1995;Rutter, 1982). The importance of a general populatiorl sample is that it avoids those distortions in associations between variables that are very common in volunteer samples or in selected samples of various kinds (e.g., Newman, Moffitt, Caspi, & Silva, 1998).…”
Section: The Dunedin Studymentioning
confidence: 99%
“…Also comorbid problems, such as substance abuse and personality disorders, are common among forensic patients. Research has shown that patients with comorbid mental disorders are more resistant to treatment, and are subject to a more chronic course and a poorer prognosis of their illness 1 . Forensic schizophrenic patients often need long-term hospitalization, and before discharge from the hospital becomes possible, clinical forensic psychiatry needs to ascertain that the patient has sufficient insight into illness, has a developed adherence with medication, and is also capable of, and motivated to maintain, long-term use of community psychiatric services 2 .…”
Section: Introductionmentioning
confidence: 99%